Accessibility Measures: From a Literature Review to a Classification Framework - Gabriella Mazzulla; Carlo Giuseppe Pirrone (ISPRS International Journal of Geo-Information)
This paper presents a comprehensive review of the accessibility measures and models used in land use and transportation planning, highlighting their evolution and recent applications. It categorizes the accessibility measures into passive and active, detailing their theoretical foundations and examining the differences between behavioral and non-behavioral models. By synthesizing the literature, this paper proposes a conceptual classification framework that integrates various accessibility measures. We aim to provide a structured classification of the accessibility measures, dividing them into various levels and grouping them into macro-areas and methodologies. This approach allows for the adaptation of the accessibility measures based on the specific study context, considering the hypotheses made beforehand and the relevant parameters for different scenarios. The findings emerging from the proposed classification framework highlight two opposite ways to measure accessibility: on the one hand, by considering the physical distance between locations, in terms of both spatial separation and proximity; on the other hand, by capturing individuals’ preferences and attitudes toward reaching goods, services or activities and then measuring the “perceived” accessibility. We underscore the necessity of considering both approaches in planning processes to create equitable and sustainable urban environments. This structured classification aims to guide researchers and planners in selecting appropriate tools tailored to specific contexts and needs, which means choosing the most appropriate accessibility measure to use, depending on the characteristics of the case being examined and the specific needs of the project.